Ondine’s curse: the origin of the myth (2020)
Central alveolar hypoventilation syndrome has been known for decades as Ondine's curse. It was named as such after a German myth. Although most of the stories resemble one another, word of mouth has led to misinterpretation of this tale among the medical community. The present paper reviews the original narrative, its characters, and how it is linked to the most relevant aspects of the disease.